Prevalence and therapeutic outcomes of intraoperative MCL injury in subjects undergoing total knee arthroplasty - Sepehr Shirouei; Mehdi Karimi; Gholamreza Ghorbani Amjad; Morteza Majidi; Niyousha Shirsalimi; Abbas Moradi (Journal of Orthopaedic Reports)
Background: Total knee arthroplasty (TKA) is a recommended procedure for replacing damaged knee joints, but it can cause intraoperative medial collateral ligament (MCL) injuries, which can affect patient recovery and surgical outcomes. This study aims to evaluate the prevalence and therapeutic outcomes for patients who sustained MCL injuries during TKA. Methods: Over two years (2015–2018), 553 patients undergoing TKA were evaluated, with 13 experiencing intraoperative MCL injuries. Following surgery, patients adhered to a partial weight-bearing protocol, wearing a locked knee brace for two weeks, followed by a six-week physiotherapy program to gradually restore knee motion. Patients were monitored for 12 months, with pre- and post-surgery assessments conducted using the International Knee Documentation Committee (IKDC) score. Data were analyzed using SPSS version 21 software. Results: The results showed a 2.35 % prevalence of intraoperative MCL injuries among 553 TKA patients, with 85 % of cases in females and 15 % in males; however, there was no significant association between MCL injury and gender (p = 0.786). Postoperatively, patients showed a statistically significant reduction in pain (mean score decrease from 90 to 3.8, p < 0.001) and improvement in knee function (mean IKDC score increase from 28.2 to 77.8, p < 0.001). No significant associations were found between IKDC scores and gender (p = 0.806) or age (p = 0.998). Additionally, there was no significant difference in IKDC scores between patients with treated MCL injuries and those without (p = 0.141). At 12-month follow-up, no knee instability or complications were reported. Conclusion: The study found that intraoperative MCL injuries in TKA patients are rare but, when properly managed, do not affect long-term outcomes. Patients showed significant improvements in pain and knee function, with no complications or instability at one-year follow-up, indicating that MCL injuries do not compromise TKA success.